Comparison of postoperative analgesia by preemptive use of intravenous paracetamol and intravenous ketorolac in patients undergoing elective laparoscopic surgeries - Syed Najeebullah Khadri; R Shankar Anand; K Soundarya Priyadharsini; T. Krishna Prasad (Journal of Current Research in Scientific Medicine)
Background: Preemptive analgesia involves the introduction of an analgesic regimen before the onset of surgical stimuli. Paracetamol and ketorolac are effective in blunting postoperative pain scores and opioid consumption, but their comparison, when used preemptively, has been less studied. The study aim to compare the clinical efficacy of intravenous (IV) paracetamol and IV ketorolac given preemptively, to blunt the postoperative pain among patients undergoing laparoscopic surgeries. Materials and Methods: This was a double-blinded randomized control study conducted on 48 patients undergoing laparoscopic surgeries, and they were allotted into groups of 24 each. Patients in Group 1 received an IV paracetamol infusion of 1 g over 10–15 min, 1 h before surgery. Group 2 received IV ketorolac 30 mg in 100 mL NS over 10–15 min, 1 h before surgery. The primary aim of the study was to monitor postoperative pain using the Visual Analog Scale (VAS). The secondary aim was to monitor the rescue analgesia with the opioid. Hemodynamics and sedation score were monitored every 2 h till 12 h postsurgery. Results: The mean time to the first rescue drug among the paracetamol group was lower and statistically significant (P < 0.05) compared to the ketorolac group. The pulse rate, VAS, mean systolic blood pressure (SBP), Mean arterial pressure (MAP), and sedation score among the paracetamol group were insignificant compared to the ketorolac group at different time intervals. Conclusion: Postoperatively, sedation was not significantly different between the groups. The pain score was significantly lower and the time to first rescue was significantly higher among the ketorolac group compared to the paracetamol group. The preemptive use of IV ketorolac provided better postoperative analgesia compared with IV paracetamol in patients undergoing elective laparoscopic surgeries.